CURRENT ISSUES IN LINGUISTICS AND TRANSLATION STUDIES: CURRENT ISSUES IN LINGUISTICS AND TRANSLATION STUDIES - Anefiyaeva, Anzhela (Журнал иностранных языков и лингвистики, 2025)
This article aims to address the current issues in both linguistics and translation studies, offering a comprehensive overview of the evolving debates and challenges that define the contemporary research and practice in these areas. Linguistics and translation studies are interdependent fields that shape and are shaped by each other. Linguistics, the scientific study of language structure, semantics, and phonology, provides essential insights into how languages function. Translation studies, on the other hand, addresses the complex process of transferring meaning from one language to another. One of the foremost issues in translation studies is the challenge of accurately conveying cultural nuances between languages. Each language carries its own set of idiomatic expressions, metaphors, and cultural references that do not always have direct equivalents in another language. The theory of dynamic equivalence, proposed by Eugene Nida, suggests that translations should prioritize the meaning over literal word-for-word translation. However, the challenge remains in balancing the integrity of the original text with the cultural expectations of the target audience.